2019
DOI: 10.1007/978-3-030-22507-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Eye-Gaze Metrics of Mental Workload in Monitoring Process Plants

Abstract: Continuous, non-invasive workload indicators of operators is an essential component for dynamically assigning appropriate amount of tasks between automation and operators to prevent overload and out-of-the-loop problems in computer-based procedures. This article examines the monitoring task difficulty manipulated by the task type and load, and explores physiological measurements in relation to mental workload. In a within-subject design experiment, forty-five university students performed monitoring tasks in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Recently, fixation duration and fixation numbers have been used in oil refinery studies (Huang et al, 2019;Salehi et al, 2018;Shi et al, 2021). Researchers have shown that number of fixations could be effective and continuous indicators of workload in a control room monitoring task (Huang et al 2019).…”
Section: Visual Behavior Measurements In Oil Refinery Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, fixation duration and fixation numbers have been used in oil refinery studies (Huang et al, 2019;Salehi et al, 2018;Shi et al, 2021). Researchers have shown that number of fixations could be effective and continuous indicators of workload in a control room monitoring task (Huang et al 2019).…”
Section: Visual Behavior Measurements In Oil Refinery Researchmentioning
confidence: 99%
“…Recently, fixation duration and fixation numbers have been used in oil refinery studies (Huang et al, 2019;Salehi et al, 2018;Shi et al, 2021). Researchers have shown that number of fixations could be effective and continuous indicators of workload in a control room monitoring task (Huang et al 2019). Moreover, Salehi et al (2018) compared novices' and experts' visual behaviors captured in real-time monitoring when they were engaged in a task with regard to abnormal situation.…”
Section: Visual Behavior Measurements In Oil Refinery Researchmentioning
confidence: 99%